FRI0130 RELATIONSHIP BETWEEN DEPRESSION AND DISEASE ACTIVITY IN US VETERANS WITH EARLY RHEUMATOID ARTHRITIS RECEIVING METHOTREXATE. (June 2019) - Rathbun, Alan; England, Bryant; Mikuls, Ted; Ryan, Alice; Barton, Jennifer; Shardell, Michelle; Gallo, Joseph; Stuart, Elizabeth; Hochberg, Marc
Abstract : Background: Depression is common in rheumatoid arthritis (RA) patients and exacerbates disease activity and may reduce response to first-line disease-modifying antirheumatic drugs. Objectives: To determine whether depression affects disease activity in patients with early RA treated with methotrexate (MTX). Methods: Patients in the Veterans Affairs Rheumatoid Arthritis registry with early RA (onset <2 years) receiving MTX were selected (n=268). Depression was assessed at baseline using International Classification of Diseases codes (296.2-296.39, 300.4, 311). Disease activity was measured using the 28 joint count disease activity score (DAS-28), tender and swollen joint counts (TJC and SJC), patient and provider global assessment (PTGA and PRGA), patient-reported pain, multidimensional health assessment questionnaire (MDHAQ), and erythrocyte sedimentation rate (ESR). Baseline confounders included sociodemographics, anthropometrics, concomitant treatments, and other clinical characteristics. Propensity score weights were used to equate the depressed and non-depressed participants on baseline confounders. Generalized linear survey models were used to compare disease activity trajectories between depressed (n=48) and non-depressed (n=220) patients over two years. Standardized causal mean outcome differences were estimated at 6 months and 1- and 2-years follow-up. Results: Depression was associated with significantly greater DAS-28 at 6 months (β=0.36; 95% CI: 0.03, 0.69) but not at 1- or 2-years follow-up (Table 1 ). Associations for DAS-28 component measures were smaller in magnitude, decreased over time, and not statistically significant. Depression was also associated with significantly greater pain at both 6 months (β=0.47; 95% CI: 0.11, 0.82) and 1-year (β=0.42; 95% CI: 0.03, 0.82) follow-up but not the PRGA or MDHAQ at any assessed time interval. Conclusion: Findings demonstrate that depression is associated with less robust short-term response to MTX, and despite clinical RA treatment, more persistent and severe pain. Depression in RA patients may be a risk factor for primary non-response to MTX treatment, and interventions targeted at treating depression could result in better initial RA disease control and DMARD persistence. Acknowledgement: This material is based on upon work supported (or supported in part) by the Department of Veterans Affairs, Veterans Health Administration, Office of Research and Development, VA Maryland Health Care System, and Baltimore VA Medical Center. Disclosure of Interests: Alan Rathbun: None declared, Bryant England: None declared, Ted Mikuls: None declared, Alice Ryan: None declared, Jennifer Barton: None declared, Michelle Shardell: None declared, Joseph Gallo: None declared, Elizabeth Stuart: None declared, Marc Hochberg Shareholder of: BriOri Biotech, Theralogix LLC., Consultant for: Bristol Myers Squibb, Eli Lilly, EMD Serono, Novartis Pharma AG, Pfizer Inc., Samumed LLC, Symic Bio Inc., Theralogix LLC, TissueGene Inc., TLC Biopharmaceuticals, Inc., Zynerba, Galapagos, IQVIA, Hoffman LaRoche.